2020
DOI: 10.1016/j.celrep.2020.108120
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2/3 Are Required for Somatic Reprogramming through Different RNA Deadenylation Pathways

Abstract: N 6 -methyladenosine (m 6 A), the most abundant reversible modification on eukaryote messenger RNA, is recognized by a series of readers, including the YT521-B homology domain family (YTHDF) proteins, which are coupled to perform physiological functions. Here, we report that YTHDF2 and YTHDF3, but not YTHDF1, are required for reprogramming of somatic cells into induced pluripotent stem cells (iPSCs). Mechanistically, we found that YTHDF3 recruits the PAN2-PAN3 deadenylase complex and conduces to reprogramming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 62 publications
(84 reference statements)
1
29
0
Order By: Relevance
“…Results obtained in the present study show that the loss of m 6 A modification contributes to lengthening the 3ʹ‐UTR of ATAF1 , GI and GSTU17 transcripts via alterations in poly(A) site usage (Figure 5). Given that the m 6 A marks in the 3ʹ‐UTR are recognized by the m 6 A reader proteins YTHDF2 and YTHDF3, which are involved in mRNA decay via the YTHDF2‐CCR4‐NOT and YTHDF3‐PAN2‐PAN3 pathways, respectively, in mammals (Du et al , 2016; Liu et al , 2020), it is highly likely that the loss of the m 6 A marks in the 3ʹ‐UTRs of the ATAF1 , GI and GSTU17 transcripts in the vir‐1 mutant renders them unrecognizable by m 6 A reader proteins, which results in 3ʹ‐UTR lengthening and a concomitant increase in the stability of these transcripts. Because the stability and integrity of m 6 A‐containing transcripts can be modulated by specific reader proteins (Pontier et al , 2019; Wei et al , 2018), it is of primary importance to further determine how different m 6 A marks are recognized by specific reader proteins, and how this interaction is associated with the stability of m 6 A‐containing transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained in the present study show that the loss of m 6 A modification contributes to lengthening the 3ʹ‐UTR of ATAF1 , GI and GSTU17 transcripts via alterations in poly(A) site usage (Figure 5). Given that the m 6 A marks in the 3ʹ‐UTR are recognized by the m 6 A reader proteins YTHDF2 and YTHDF3, which are involved in mRNA decay via the YTHDF2‐CCR4‐NOT and YTHDF3‐PAN2‐PAN3 pathways, respectively, in mammals (Du et al , 2016; Liu et al , 2020), it is highly likely that the loss of the m 6 A marks in the 3ʹ‐UTRs of the ATAF1 , GI and GSTU17 transcripts in the vir‐1 mutant renders them unrecognizable by m 6 A reader proteins, which results in 3ʹ‐UTR lengthening and a concomitant increase in the stability of these transcripts. Because the stability and integrity of m 6 A‐containing transcripts can be modulated by specific reader proteins (Pontier et al , 2019; Wei et al , 2018), it is of primary importance to further determine how different m 6 A marks are recognized by specific reader proteins, and how this interaction is associated with the stability of m 6 A‐containing transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that YTHDF2/3, but not YTHDF1, regulate the MET event in somatic cell reprogramming in an m 6 A dependent manner through the Hippo signaling pathway effector Tead2 [44]. Other studies have shown redundancy among the three paralogs Ythdf1/2/3, suggesting they can have adequate functional compensation at least in some biological contexts [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, m 6 A-methylated mRNAs can be also decayed by YTHDF2-Heat-responsive protein 12 (HRSP12)-RNase P/MRP-mediated endoribonucleolytic cleavage (20). Moreover, YTHDF3 can induce m 6 A-decorated mRNAs deadenylation and sequent decay by recruiting PAN2-PAN3 deadenylase complex (28). Nonetheless, accumulating evidence also indicate that several m 6 A-readers, including IGF2BPs, FMRP and Prrc2a, can conversely enhance stability of m 6 A-containg mRNA (29)(30)(31).…”
Section: The M 6 A-mediated Biological Functionsmentioning
confidence: 99%